Exploring the relationship between types of leisure activities and acculturation among Korean immigrants. Issue 1 (2nd January 2016) - Kim, Junhyoung; Heo, Jinmoo; Lee, Chungsup
Abstract : Research has suggested that leisure engagement facilitates acculturation among immigrants. A dearth of information exists about which types of leisure activities are associated with acculturation among immigrants. This study focused on 434 Korean immigrants in order to determine what types of leisure activities were associated with behavioural acculturation (e.g. language usage and social context) and cultural value acculturation (e.g. collectivism, self-control and success). The results showed that participation in hobbies and indoor activities were the positive predictors of behavioural acculturation, while engagement in cultural and volunteer activities was the negative predictors of behavioural acculturation. In addition, cultural value acculturation had a positive association with social activity engagement, but had a negative association with participation in physical, cultural and volunteering activities. Overall, these findings indicated that engaging in leisure activities is positively associated with acculturation. This study suggests that leisure engagement can be beneficial in the successful acculturation process of the Korean immigrant in Western society.